Embryonic and Postnatal Expression of Aryl Hydrocarbon Receptor mRNA in Mouse Brain - Kimura, Eiki; Tohyama, Chiharu (Frontiers in Neuroanatomy, 2017)
Aryl hydrocarbon receptor (AhR), a member of the basic helix-loop-helix-Per-Arnt-Sim transcription factor family, plays a critical role in the developing nervous system of invertebrates and vertebrates. Dioxin, a ubiquitous environmental pollutant, avidly binds to this receptor, and maternal exposure to dioxin has been shown to impair higher brain functions and dendritic morphogenesis, possibly via an AhR-dependent mechanism. However, there is little information on AhR expression in the developing mammalian brain. To address this issue, the present study analyzed AhR mRNA expression in the brains of embryonic, juvenile, and adult mice by reverse transcription (RT)-PCR and in situ hybridization. In early brain development (embryonic day 12.5), AhR transcript was detected in the innermost cortical layer. The mRNA was also expressed in the hippocampus, cerebral cortex, cerebellum, olfactory bulb, and rostral migratory stream on embryonic day 18.5, postnatal days 3, 7, and 14, and in 12-week-old (adult) mice. Hippocampal expression was abundant in the CA1 and CA3 pyramidal and dentate gyrus granule cell layers, where expression level of AhR mRNA in 12-week old is higher than that in 7-day old. These results reveal temporal and spatial patterns of AhR mRNA expression in the mouse brain, providing the information that may contribute to the elucidation of the physiologic and toxicologic significance of AhR in the developing brain.